ضمانات مشروعية القرار التأديبي لعضو هيئة التدريس الجامعي خلال مرحلة التحقيق الإداري في القانون الليبي = Guarantees of the legality of the disciplinary decision of the university faculty member during the stage of administrative investigation in the Libyan law - Rawiha, Abdelhakim Emhemed; Sadique, Muhammad Abdurrahman (Penerbit USIM, Universiti Sains Islam Malaysia (USIM), 2018)
لم يترك القانون الليبي عضو هيئة التدريس الجامعي بصفة كموظف عام يقع تحت طائلة تغول السلطة التقديرية لجهة الإدارة فيما يتعلق بالتأديب، حيث ألزمها المشرع باتباع مجموعة من الضمانات الشكلية والموضوعية يترتب على مخالفتها بطلان كافة إجراءات التحقيق والتأديب الإداريين، ولتوضيح ذلك سيتناول البحث مفهوم المخالفة التأديبية التي يرتكبها عضو هيئة التدريس الجامعي في القانون الليبي بمناسبة أدائه لوظيفته وذلك من حيث تحديد ماهيتها وأركانها والعلاقة بينها وبين الجريمة الجنائية، وأيضا تحديد ماهية التحقيق الإداري الذي تباشره جهة الإدارة مع عضو هيئة التدريس نتيجة ارتكابها للمخالفة التأديبية وأوجه التشابه والاختلاف بين التحقيق الإداري والتحقيق الجنائي، بالإضافة إلى ذلك يتناول البحث توضيح أهم الضمانات الشكلية والموضوعية التي ألزم القانون الليبي جهة الإدارة اتباعها أثناء مباشرة التحقيق مع عضو هيئة التدريس الجامعي، ويستخدم الباحث المنهج التحليلي والاستدلالي وذلك من خلال تحليل النصوص القانونية المرتبطة بالتحقيق الإداري وضماناته والاستدلال بأحكام محاكم القضاء الإداري الليبية للوصول إلى النتائج المرجوة من البحث، وقد توصل البحث إلى نتيجة مفادها أن سلطة جهة الإدارة تتقيد فيما يتعلق باتباع الضمانات الشكلية والموضوعية بحيث يبرتب على عدم اتباعها بطلان القرار التأديبي الصادر عنها بحق عضو هيئة التدريس لكون هذه الضمانات مرتبطة بالنظام العام. ******************************************************* The Libyan law did not leave the university faculty member in his capacity as a public servant under the authority of the administrative authority in terms of discipline. The legislator obliged them to follow a set of formal and objective guarantees that would result in violating all administrative investigation and disciplinary procedures. Which is committed by a member of the university faculty in the Libyan law on the performance of his job in terms of determining the nature and elements and relationship between them and criminal crime, and also determine the nature of the administrative investigation conducted by the management with a member of the Board of Teaching the result of the disciplinary offense and the similarities and differences between administrative investigation and criminal investigation. In addition, the research deals with clarifying the most important formal and objective guarantees that the Libyan law requires the administration to follow during the investigation of the university faculty member. The researcher uses analytical and analytical methods Through the analysis of the legal texts related to the administrative investigation and its guarantees and the reasoning of the courts of the Libyan administrative courts to reach the desired results, and the research concluded that the authority of the management is bound to follow the attachment And not to follow the invalidity of the disciplinary decision issued against the faculty member because these guarantees are linked to public order.